Write an English phrase that would translate into the following mathematical expression.
6z-8
19 answers
The product of 6 and z, subtracted by 8.
Translate to an algebraic expression.
9 less than t
9 less than t
t - 9
Write the phrase as a mathematical expression. 6 more than 2 times x
2x + 6
Write an algebraic expression for the following word phrase. 8.61 less than the product of 42 and x
42x - 8.61
A bagel shop sells bagels by the baker's dozen. The table at the right shows the number of bagels a shop gives per "baker's dozen" ordered. Write an algebraic expression that gives the rule for finding the number of bagels in any number b of baker's dozens.
The algebraic expression that gives the rule for finding the number of bagels in any number b of baker's dozens is:
13b
13b
3(x^2+5) is an example of which of the following?
The expression 3(x^2+5) is an example of a simplified algebraic expression.
Simplify the expression.
(4^2-2^3) divided by 7
(4^2-2^3) divided by 7
To simplify the expression (4^2-2^3) divided by 7, we can start by evaluating the exponents:
(4^2-2^3) divided by 7
= (16 - 8) divided by 7
Next, we perform the subtraction:
= 8 divided by 7
Therefore, the simplified expression is 8/7.
(4^2-2^3) divided by 7
= (16 - 8) divided by 7
Next, we perform the subtraction:
= 8 divided by 7
Therefore, the simplified expression is 8/7.
evaluate (4/9)^2
To evaluate (4/9)^2, we square the fraction (4/9):
(4/9)^2 = (4/9) x (4/9) = 16/81
Thus, (4/9)^2 equals 16/81.
(4/9)^2 = (4/9) x (4/9) = 16/81
Thus, (4/9)^2 equals 16/81.
Evaluate the expression below for s = 2 and t = 7.
4st^2 - s^2 =
4st^2 - s^2 =
To evaluate the expression 4st^2 - s^2 for s = 2 and t = 7, we substitute those values into the expression:
4(2)(7)^2 - (2)^2
= 4(2)(49) - 4
= 392 - 4
= 388
Therefore, when s = 2 and t = 7, the expression 4st^2 - s^2 evaluates to 388.
4(2)(7)^2 - (2)^2
= 4(2)(49) - 4
= 392 - 4
= 388
Therefore, when s = 2 and t = 7, the expression 4st^2 - s^2 evaluates to 388.
Simplify the following expression. 3[(9-6)^5 divided by 9]
To simplify the expression 3[(9-6)^5 divided by 9], we start by evaluating the exponent inside the parentheses:
(9-6)^5 = 3^5 = 243
Next, we divide 243 by 9:
243 divided by 9 = 27
Finally, we multiply 27 by 3:
3 × 27 = 81
Therefore, the simplified expression is 81.
(9-6)^5 = 3^5 = 243
Next, we divide 243 by 9:
243 divided by 9 = 27
Finally, we multiply 27 by 3:
3 × 27 = 81
Therefore, the simplified expression is 81.